Invalidity Juridical Acts and Its Classification - Abduli, Entela (European Journal of Multidisciplinary Studies, 2016)
Based on the kind of invalidity juridical acts and contracts in Albanian Law are generally classified in absolute and relative invalid acts. The difference between them and the consequences are defined in Albanian Civil Code. Invalidity of juridical as a very important aspect of rights was first mentioned in traditional albanian system of rules and then defined in Civil Code of 1929 of King Zogu “About juridical acts and obligations”,Civil Code of National Albanian Republic of 1981 and actual Civil Code of 1994. This work aims to analyze classification of invalid juridical acts and the elements that cause this invalidity. For this purpose are taken into consideration actual juridical literature, laws and their changes, Unified sentences of Supreme Tribunal Court and collected database from different courts. While analyzing this database the question that arises is: whether classification of invalid juridical acts is important in adjusting consequences derived from these acts.